Reator airlift operado em sobrepressão: construção, caracterização da transferência de oxigênio e aplicação em cultivos de Escherichia coli recombinante - Campani Junior, Gilson (Universidade Federal de São Carlos, 2014)
Owing to the broad biochemical, physiological and genetic characterization and the ease of manipulation and cultivation, several proteins with therapeutic and industrial applications are produced by genetically modified Escherichia coli. There is abundant information in the literature about strategies to increase biomass and recombinant protein production by cultivation of E. coli employing stirred and aerated tank bioreactor (conventional type). In contrast, although quite employed in cultivation of filamentous microorganisms, there are just a few studies involving cultivation of E. coli in airlift bioreactor. This reactor offers advantages over conventional one, such as simplicity of construction, reduced risk of contamination and efficient gas-liquid dispersion with low power consumption. However, the lower O2 transfer in airlift bioreactor (bench scale), compared to that achieved in conventional one, justifies the manipulation of temperature, pressure and flow rates of air and O2 in the dissolved oxygen concentration (DOC) control, avoiding decreases in biomass and recombinant protein productivities. In this context, this study aimed to: (i) determine the influence of internal pressure on the gas holdup (ɛ), volumetric O2 transfer coefficient (kLa) and volumetric O2 transfer rate (continue...).
Keywords: Produção de PspA; Operação em sobrepressão; Airlift; Escherichia coli; Cultivo Celular; Controle; Transferência de Oxigênio; Cell cultivation; Control; Oxygen transfer; Overpressure; ENGENHARIAS::ENGENHARIA QUIMICA